Attitudes and Perspectives of Teacher Performers on Pedagogy and Perceived Student Learning in the Elementary and Secondary School Music Classroom - Vitale, John L. (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
This study investigated the lives of three active music teacher performers and how their performing experience impacted pedagogy and perceived student learning in the classroom. At the time of data collection, one participant was a full-time elementary school music teacher, and the other two participants were full-time secondary school music teachers. Philosophically, this study intended to discover the central meaning underlying the life experiences of each participant as they relate to pedagogy and perceived student learning (phenomenology). Methodologically, qualitative data (typical of phenomenological inquiry) were collected through both interviews and a focus group session. Furthermore, a traditional thematic exploration of the data was employed. Findings indicate that pedagogy and perceived student learning are positively impacted through the theme of respect and negatively impacted through the themes of fatigue and job dissatisfaction. Such themes invite all educators within the performing arts to reexamine and reflect upon the intricate relationship between performing and teaching.